Percutaneous thrombectomy of fat embolism in-transit - Erin Cihat Saricilar, BMed, MD, MS, MM; Cartan Costello, MB, BCH, BAO, FCICM, FACRRM, FRACGP, DRANZCOG; Alexander Misono, MD, MBA, RPVI; Laurencia Villalba, MD, FRACS Vasc (Journal of Vascular Surgery Cases and Innovative Techniques)
We report the case of a previously independent 82-year-old female who experienced acute hemodynamic and respiratory deterioration requiring inotropic support due to a fat embolism during revision hip arthroplasty. Computed tomography pulmonary angiography demonstrated fat embolism, and transesophageal echocardiogram showed evidence of right ventricle strain and fat embolism in-transit in the right heart, as well as a moderate patent foramen ovale. Under transesophageal echocardiogram and intravascular ultrasound guidance, the Inari FlowTriever thrombectomy device was used successfully to retrieve the fat embolism with immediate hemodynamic improvement, no complications, and uneventful recovery.